The aporia of freedom - Kaczmarczyk, Michał 1978- (Brill, 2023)
"The Aporia of Freedom systematizes social theories in a new manner, alternative both to the pluralistic concept, according to which social theories are incommensurable, and to the concept which postulates a theoretical synthesis in social sciences. Kaczmarczyk argues that famous social theories constitute interrelated attempts to solve the same problem, called the aporia of freedom. The problem concerns the relation between existential assumptions of social determinism and human freedom. Although these ideas turn out to be mutually exclusive, they seem to be necessary for the construction of a coherent and empirically convincing social theory"--
Keywords: Freiheit; Aporie; Soziologie; Liberty; Liberty / Social aspects